2009
DOI: 10.1002/ijc.24330
|View full text |Cite
|
Sign up to set email alerts
|

An orthotopic endometrial cancer mouse model demonstrates a role for RUNX1 in distant metastasis

Abstract: Endometrial carcinoma is the most common malignancy of the female genital tract in industrialized countries. Metastasis is the major cause of endometrial cancer deaths. Therefore, there is a vital need for clinically relevant in vivo models allowing the elucidation of the molecular and cellular mechanisms underlying metastatic behavior. In this study, we describe an innovative experimental orthotopic model of human endometrial carcinoma. Implantation in the bifurcation of the uterine horns resulted in tumors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 36 publications
1
45
1
Order By: Relevance
“…The link of bulge cell proliferation with tumorigenesis has been a recurring theme in the field, and Runx1 is a known cancer gene in blood (8,39). Runx1 mutations have been associated with acute myeloid leukemia (8), and recently Runx1 was found to be expressed and play a role in endometrial carcinoma in humans (16). Here we have implicated Runx1 in the repression of Cdkn1a (p21), known for its role in stem cell proliferation (see above), for tumor suppression downstream of p53 (31), and in the skin for blocking tumorigenesis in response to DMBA/TPA treatment (58).…”
Section: Discussionmentioning
confidence: 99%
“…The link of bulge cell proliferation with tumorigenesis has been a recurring theme in the field, and Runx1 is a known cancer gene in blood (8,39). Runx1 mutations have been associated with acute myeloid leukemia (8), and recently Runx1 was found to be expressed and play a role in endometrial carcinoma in humans (16). Here we have implicated Runx1 in the repression of Cdkn1a (p21), known for its role in stem cell proliferation (see above), for tumor suppression downstream of p53 (31), and in the skin for blocking tumorigenesis in response to DMBA/TPA treatment (58).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the characterization of molecular events associated with the development of type I and type II endometrial carcinoma such as alterations in PTEN, b-catenin, KRAS, p53, or HER-2/neu, the molecular pathology of myometrial infiltration that defines the initial steps of invasion in endometrial carcinoma is almost unknown (12,22,23). Thus, an important clinical impact would be associated with discovering genes or canonical pathways associated with advanced endometrial carcinomas, unmasking the principal common mechanisms of tumor aggressiveness, providing novel markers and developing rational therapies.…”
Section: Discussionmentioning
confidence: 99%
“…This cell line has been described as TGF-b1 sensitive and its metastatic ability partially depends on the correct activation of this route (20). Moreover, our group showed that when injected in mice either subcutaneously or orthotopically, HEC-1A cells generate highly undifferentiated and aggressive tumors representative of high-risk endometrial carcinoma (12). Cells treated with TGF-b1 (2.5 ng/mL) for 24 hours acquired a mesenchymal phenotype characterized by the loss of cell-cell contacts and the promotion of migratory structures as lamellipodia ( Fig.…”
Section: Tgf-b1 Promotes Emt In Endometrial Cancer Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…These two markers have been found to be deregulated in different types of tumors, including endometrioid, prostate, breast and oral squamous carcinoma together with acute lymphoblastic leukemia (8,9,11,12,14,(18)(19)(20)(21)(22)(23)(24)(25). The present study was designed to address the hypothesis of cohesin deregulation in endometrial cancer.…”
Section: Introductionmentioning
confidence: 98%